The prevalence of metabolic syndrome in patients with non-alcoholic fatty liver disease in primary care clinics at King Saud University Medical City, Riyadh, Saudi Arabia - Alyousef, Alanoud Maan; Mekawy, Doaa Zeinhom; Bashumeel, Yaser Yousef; Mohamed, Saleh Magdy; Almigbal, Turky H.; Batais, Mohammed A.; Alrasheed, Abdullah A. (Frontiers in Endocrinology, 2025)
BackgroundMetabolic syndrome is present in a subset of individuals harboring a constellation of metabolic risk factors that heightens their likelihood of developing coronary artery disease. Non-alcoholic fatty liver disease (NAFLD) manifests through the incremental accumulation of fat within liver cells in the absence of secondary causes. NAFLD has long been recognized as the hepatic manifestation of metabolic syndrome. Our study seeks to ascertain the prevalence of metabolic syndrome among NAFLD patients at King Khalid University Hospital and to explore the factors associated with metabolic syndrome.Method and designWe conducted a retrospective study targeting 1,173 patients diagnosed with NAFLD at King Khalid University Hospital in Riyadh, Saudi Arabia, from March 2020 to March 2021. NAFLD diagnosis was made based on ultrasonographic evidence of a fatty liver, excluding other liver ailments and alcohol intake. Metabolic syndrome was defined according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP/ATP III) criteria, which require at least three of five metabolic risk factors to be present. Statistical analysis was performed using chi-square tests for categorical variables and independent t-tests for continuous variables, with a significance level set at p < 0.05.ResultsOut of 1173 NAFLD participants evaluated, 38.2% met the NCEP/ATPIII criteria for metabolic syndrome. Additionally, 23.8% had at least one metabolic syndrome component coinciding with their ultrasonographically confirmed NAFLD diagnosis. The incidence of NAFLD was not linked to gender. Married individuals constituted a higher percentage (42.8%) of the NAFLD cohort. Elevated blood glucose and triglyceride levels, along with reduced HDL levels, were predominantly observed among the metabolic syndrome components in NAFLD patients.ConclusionA significant portion of the NAFLD patient population was concurrently affected by metabolic syndrome. There exists a marked interrelationship between NAFLD and the components of metabolic syndrome. Regular metabolic disorder screenings are recommended for this patient group.